Midterm Results of Proximal Aneurysm Sealing With the Ovation Stent-Graft According to On- vs Off-Label Use. (April 2017) - de Donato, Gianmarco; Setacci, Francesco; Bresadola, Luciano; Castelli, Patrizio; Chiesa, Roberto; Mangialardi, Nicola; Nano, Giovanni; Setacci, Carlo
Purpose: To compare the use of the Ovation stent-graft according to the ≥7-mm neck length specified by the original instructions for use (IFU) vs those treated off-label (OL) for necks <7 mm long.Methods: A multicenter retrospective registry (TriVascular Ovation Italian Study) database of all patients who underwent endovascular aneurysm repair with the Ovation endograft at 13 centers in Italy was interrogated to identify patients with a minimum computed tomography (CT) follow-up of 24 months, retrieving records on 89 patients (mean age 76.4±2.4 years; 84 men) with a mean follow-up of 32 months (range 24–50). Standard CT scans (preoperative, 1-month postoperative, and latest follow-up) were reviewed by an independent core laboratory for morphological changes. For analysis, patients were stratified into 2 groups based on proximal neck length ≥7 mm (IFU group, n=57) or <7 mm (OL group, n=32). Outcome measures included freedom from type Ia endoleak, any device-related reintervention, migration, and neck enlargement (>2 mm).Results: At 3 years, there was no aneurysm-related death, rupture, stent-graft migration, or neck enlargement. There were no differences in terms of freedom from type Ia endoleak (98.2% IFU vs 96.8% OL, p=0.6; hazard ratio [HR] 0.55, 95% CI 0.02 to 9.71 or freedom from any device-related reintervention (92.8% IFU vs 96.4% OL, p=0.4; HR 2.42, 95% CI 0.34 to 12.99). In the sealing zone, the mean change in diameters was −0.05±0.8 mm in the IFU group and −0.1±0.5 mm in the OL group.Conclusion: Use of the Ovation stent-graft in patients with neck length <7 mm achieved midterm outcomes similar to patients with ≥7-mm-long necks. These midterm data show that the use of the Ovation system for the treatment of infrarenal abdominal aortic aneurysm is not restricted by the conventional measurement of aortic neck length, affirming the recent Food and Drug Administration–approved changes to the IFU.